Contemporary Digital Technologies of Media Communication in Social Media: A Typological Classification - Бондар, Юрій Володимирович; Штельмах, Павло (Київський національний університет імені Тараса Шевченка, 2025)
The study examines the latest communication technologies of the digital age, which are changing the ways and effectiveness of conveying information to the media audience. Scientific literature shows fragmentation in defining the boundaries, terminology, and classification of means of conveying information in the digital age, which necessitates a unified approach to analyzing the latest communication practices. The purpose of this article is to review existing research on contemporary technologies in mass communication, to classify the latest technologies for conveying information in the digital environment and to identify the key vectors of their application in the context of mass communication. The authors consider social media, streaming services, and the latest television, some advertising platforms, automatic translation tools, analytics, and crowdsourcing platforms as part of the latest communication technologies. The methodology is based on theoretical analysis, content analysis, typological, and comparative methods. The study proposes a typological structure of the contemporary communication technologies based on the following criteria: communication format, degree of automation, role of the audience, nature of personalization, and algorithmic control. The results of the study can be applied in future detailed studies on the development of media management, information policy, and digital security strategies. They also contribute to the formation of a scientific basis for further research in media communications in the context of the modern digital transformations.

У дослідженні розглядаються новітні технології комунікації цифрової епохи, що змінюють способи та ефективність донесення інформації до аудиторії ЗМК. У науковій літературі спостерігається фрагментарність у визначенні меж, термінології та класифікації засобів донесення інформації у цифрову добу, що зумовлює потребу в уніфікованому підході до аналізу новітніх комунікаційних практик. Мета статті – оглянути наукову літературу, що стосується теми сучасних технологій масової комунікації, здійснити класифікацію новітніх технологій донесення інформації в цифровому середовищі та визначити ключові вектори їх застосування в контексті масової комунікації. Автори розглядають соціальні медіа, стримінгові сервіси, деякі рекламні платформи, інструменти автоматичного перекладу, платформи аналітики та краудсорсингу як частину сучасних комунікаційних технологій. Методологія базується на теоретичному аналізі, контент-аналізі, типологічному та порівняльному методах. У межах дослідження сформовано типологічну структуру новітніх технологій комунікування за критеріями: формат комунікації, ступінь автоматизації, роль аудиторії, характер персоналізації та алгоритмічного контролю. Результати дослідження можуть бути застосовані в розробці стратегій медіаменеджменту, інформаційної політики та цифрової безпеки. Вони також сприяють формуванню наукового базису для подальших досліджень у сфері медіакомунікацій в умовах цифрової трансформації соціальних комунікацій.
Сучасні цифрові технології медіакомунікації в соціальних мережах: типологічна класифікація
Keywords: social media; modern digital technologies; new information technologies; social networks; streaming platforms; технології; соціальні медіа; сучасні цифрові технології; новітні інформаційні технології; соціальні мережі; стримінгові платформи